Application of Good Corporate Governance (GCG) in State-Owned Enterprises - Lusiana Margareth Tijow; Hayat Hayat (Universitas Muhammadiyah Ponorogo, 2021)
The implementation of GCG is important for companies to carry out careful phasing based on an analysis of the situation and condition of the company, and the level of readiness, so that GCG implementation can run smoothly and get support from all elements within the company. As a step to improve performance, efficiency and professionalism, then emerged a principle that is believed to encourage an increase in the performance of the company, this principle is the principle of Good Corporate Governance (GCG). GCG is defined as a system that regulates and controls a company to create value added for all stakeholders, including in its application to State-Owned Enterprises (SOEs). The obstacles that often prevent SOEs from functioning economically are the government itself and the poor quality of human resources and a corporate culture that tends to be KKN. To avoid greater losses, it is necessary to change the management of SOEs. In terms of legal material, legal structure and legal culture as well as problems arising from its implementation by presenting a new SOEs law using the principles of GCG. This study employs normative legal research using qualitative juridical analysis methods. The role of State-Owned Enterprises in the national economy in realizing people's welfare is not optimal. SOEs plays a role in producing the goods and or services needed in order to realize the greatest prosperity of the community.